2016
DOI: 10.1016/j.biocel.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Poly C binding protein 1 represses autophagy through downregulation of LC3B to promote tumor cell apoptosis in starvation

Abstract: Accumulating evidences indicate that poly C binding protein (PCBP1) is downregulated in various carcinomas as a tumor suppressor, but the underlying mechanism in suppression of tumorigenesis still remains elusive. Here, we found that PCBP1 overexpression attenuates tumor cell growth upon serum-free starvation. Notably, the autophagic degradation inhibitor, chloroquine, could mimic this suppressive effect in tumor cell growth. Autophagy analyses demonstrated that PCBP1 overexpression blocked autophagic flux of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…The downexpression of HSPA1A could be explained considering the reduction of the synthesis of proteins substrate of Hsp70. [48,[150][151][152][153][154][155][156][157][158][159][160][161][162][163] SMALL GTPASE SUPERFAMILY ALTERED SIGNALLING Under stress conditions KRAS (already known to be involved in Noonan syndrome) upregulation could determine an uncontrolled RPE cell proliferation or functional alterations.…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…The downexpression of HSPA1A could be explained considering the reduction of the synthesis of proteins substrate of Hsp70. [48,[150][151][152][153][154][155][156][157][158][159][160][161][162][163] SMALL GTPASE SUPERFAMILY ALTERED SIGNALLING Under stress conditions KRAS (already known to be involved in Noonan syndrome) upregulation could determine an uncontrolled RPE cell proliferation or functional alterations.…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…HnRNP E1 has been proven to promote cell apoptosis in several cancer cell lines [20][21][22]. Recently, a research group reported that hnRNP E1 repressed autophagy through downregulation of LC3B to promote tumor cell apoptosis [23]. In endothelial cells, hnRNP E1 serves as a key protective mechanism through increasing human endothelial nitric oxide synthase (eNOS) mRNA stability and we found hnRNP E1 is a new regulator of endothelium-protein disulphide isomerase translation in oxLDL-activated VECs [24,25].…”
Section: Ivyspringmentioning
confidence: 66%
“…A growing body of evidence has shown that hnRNP E1 is a tumor suppressor through regulating many cancer-related genes expression [33]. Especially, hnRNP E1 repressed autophagy and promoted apoptosis in ovary tumors [23]. In normal endothelial cells, hnRNP E1 increased the eNOS, which was involved in the maintenance of homeostasis in the blood vessel wall, mRNA stability and protein expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…The other paper suggested that PCBP1 was responsible for stabilizing gastrin mRNA which was highly expressed in colorectal adenocarcinoma (38). PCBP1 represses autophagymediated cell survival and inhibition of tumor cell autophagy and the PCBP1 upregulation may be an effective therapeutic strategy to colon tumor with low PCBP1 expression (39). LIFR(p=4.90e-04) had 4 hit papers and encodes protein that belongs to the type I cytokine receptor family.…”
Section: Genes Significant Only In An Individual Cancermentioning
confidence: 99%